2020
DOI: 10.3390/biom10050714
|View full text |Cite
|
Sign up to set email alerts
|

Phage Display Selection, Identification, and Characterization of Novel Pancreatic Cancer Targeting Peptides

Abstract: Pancreatic cancer is characterized by a 5-year survival rate of 3%, in part due to inadequate detection methods. The small size of peptides offers advantages regarding molecular targeting. Thus, peptides may be used in detection of pancreatic cancer. Here, peptides that target pancreatic cancer cells were selected using phage display technology using a 15-mer fUSE5 library. Phage were pre-cleared against immortalized pancreatic cells (hTERT-HPNE), followed by selections against pancreatic cancer (Mia Paca-2) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…[64][65][66] In preliminary studies, researchers explored the utility of phages for delivery of anticancer drugs to pancreatic cancers and demonstrated early viability of successful targeting of pancreatic tumour cells. [67][68][69] Whereas substantial data demonstrate the effect of phages on regulation of microbial population dynamics, evidence of their direct effects on human health is limited. Technical limitations in therapeutically using phages, such as dosing, route of administration, tolerance by the host immune system, and specificity to pancreatic cancer microbes and tumour antigens, remain to be addressed before this strategy can be widely adopted.…”
Section: Leading Articlementioning
confidence: 99%
“…[64][65][66] In preliminary studies, researchers explored the utility of phages for delivery of anticancer drugs to pancreatic cancers and demonstrated early viability of successful targeting of pancreatic tumour cells. [67][68][69] Whereas substantial data demonstrate the effect of phages on regulation of microbial population dynamics, evidence of their direct effects on human health is limited. Technical limitations in therapeutically using phages, such as dosing, route of administration, tolerance by the host immune system, and specificity to pancreatic cancer microbes and tumour antigens, remain to be addressed before this strategy can be widely adopted.…”
Section: Leading Articlementioning
confidence: 99%
“…Phage display technology has not only been successfully applied in various biomedical fields such as molecular imaging (Haque et al 2019 ), vaccine development (Toledo-Machado et al 2015 ), antibody engineering (Muchima et al 2018 ) and nanotechnology (Hofmeister et al 2015 ), but also shown its unique advantages in the detection of tumor-specific target molecules and targeted therapies. Studies have shown that peptide probes with high specificity and affinity have been identified for cervical cancer (Xiao et al 2019 ), breast cancer (Liu et al 2019 ), pancreatic cancer (Asar et al 2020 ), colon cancer (Kwak et al 2020 a) and esophageal cancer (Ma et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, early studies have shown that bacteriophages are able to successfully penetrate pancreatic tumors for efficient drug delivery. 85,86…”
Section: Bacteriophagementioning
confidence: 99%
“…Pancreatic ductal adenocarcinoma is notoriously a difficult tumor for effective drug penetration and delivery. However, early studies have shown that bacteriophages are able to successfully penetrate pancreatic tumors for efficient drug delivery 85,86 …”
Section: Microbial Modification For Therapeutic Potential In Pancreat...mentioning
confidence: 99%